Protein and Water Distribution Across Visual Axis in Mouse Lens: A Confocal Raman MicroSpectroscopic Study for Cold Cataract - Li, Yao; Li, Yuxing; Liu, Xi; He, Yonghong; Guan, Tian (Frontiers in Chemistry, 2021)
Purpose: To investigate cellular mechanisms of cold cataract in young lenses of wild-type C57BL/6J (B6WT) mice treated at different temperatures. To test a hypothesis that cold cataract formation is associated with the changes of lens protein and water distribution at different regions across lens fiber cells by Raman spectroscopy (RS). Methods: RS was utilized to scan the mouse lens at different regions with/without cold cataract. Three regions with various opacification along equatorial axis in anterior-posterior lens section were scanned. The intensity ratio of Raman bands at 2935 cm-1 and 3390 cm-1 (Ip/Iw) were used to evaluate lens protein and water distribution. We further determined water molecular changes through Gaussian profiles of water Raman spectra. Results: Three specific regions 1, 2 and 3, located at 790-809, 515-534 and 415-434 μm away from the lens center, of postnatal day 14 B6WT lenses, were subjected to RS analysis. At 37 °C, all three regions were transparent. At 25 °C, only region 3 became opaque, while under 4 °C, both region 2 and 3 showed opaque. The sum of the difference between Ip/Iw and the value of linear fitting line from scattered-line at each scanning point was considered as fluctuation degree (FD) in each region. Among different temperatures, opaque regions showed relatively higher FD values (0.63 and 0.79 for region 2 and 3 at 4 °C, 0.53 for region 3 at 25 °C) while transparent regions provided lower FD values (less than 0.27). In addition, the decrease of Gaussian peak II and the rising of Gaussian peak III and IV from water Raman spectra indicated the unstable of water molecule structure in the regions with cold cataract. Conclusions: Fluctuation degrees of RS data reveal new mechanistic information about cold cataract formation, which is associated with uneven distribution of lens proteins and water across lens fiber cells. It is possible that RS data partly reveals cold temperature-induced redistribution of lens proteins such as intermediate filaments in inner fiber cells. This lens protein redistribution might be related to unstable structure of water molecules according to Gaussian profiles of water RS.